Design of deep water oil subsea pipeline in Malaysian Seas [electronic resource] - Muhammad Najee Junaidi, 1993-, author 643873 (2016)
Project Paper (Sarjana Muda Sains (Rekabentuk Industri)) - Universiti Teknologi Malaysia, 2016